KOORDINASI FUNGSIONAL ANTARA POLRI DAN KEJAKSAAN PADA TAHAP PRAPENUNTUTAN TINDAK PIDANA KORUPSI (Studi Pada Polres Pasaman Barat dan Kejaksaan Negeri Pasaman Barat) - Agus Syahputra (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Article 14 letter b Act no. 8 Year 1981 About Criminal Procedure Code (KUHAP) regulates about pre-prosecution. Coordination between the investigator and the general practitioner is often the cause of delay in corruption cases, as well as in the Western Occupation. The problem is the form of functional coordination between Police investigators and the Attorney Office in the current pre-crisis stages of corruption as well as the ideal form of functional coordination between Police investigators and the Attorney Office in the preprosecution stage of corruption. The research method is analytical descriptive with empirical juridical approach. Data that is used is secondary data and primary data, while data collection technique with field study through interview for primary data and literature study for secondary data. The data obtained in the analysis is qualitative and presented in an analytical decriptive form. The result of the research shows the functional coordination between Police investigators and the Attorney at the pre-crisis stage of corruption is a continuous functional coordination. Delays in the process of completing case files by investigators often occur because of the difficulty of collecting evidence on corruption. The ideal form of functional coordination between Polri and Attorney investigators at the pre-crisis stage of corruption is the coordination and functional consolidation.